Comparisons of clinical features and outcomes between Elizabethkingia meningoseptica and other glucose non-fermenting Gram-negative bacilli bacteremia in adult ICU patients - Wei-Chih Chen; Yen-Wen Chen; Hsin-Kuo Ko; Wen-Kuang Yu; Kuang-Yao Yang (Journal of Microbiology, Immunology and Infection, 2020)
Background: Clinical information of Elizabethkingia meningoseptica (EM) bacteremia in intensive care unit (ICU) patients is limited and the impact on outcomes uncertain. The aim of this study was to investigate the clinical features and impact of EM bacteremia compared to other glucose non-fermenting Gram-negative bacilli (GNF-GNB) bacteremia in ICU patients. Methods: This retrospective cohort study enrolled 70 patients who developed GNF-GNB bacteremia after ICU admission, including 19 cases of EM bacteremia (19/70, 27.1%). The main outcome measure was in-hospital mortality. Results: The patients with EM bacteremia had a lower rate of appropriate antibiotic therapy (15.8% vs. 62.7%, p < 0.001) and a longer time to appropriate antibiotic therapy (76.8 ± 46.4 vs. 35.1 ± 38.7 h, p < 0.001), but with a less severity in acute physiology and chronic health evaluation (APACHE) II score and shock status (p < 0.05) at the onset of bacteremia, compared to those with non-EM bacteremia. The in-hospital mortality between those with EM bacteremia and non-EM bacteremia was similar (63.2% vs. 51.0%, p = 0.363). However, primary bacteremia was more frequently noted in EM compared with non-EM group (57.9% vs. 25.5%, p = 0.011), and odds ratio 4.294 (95% confidence interval 1.292–14.277, p = 0.017) in multivariate regression analysis. Conclusion: Among the patients with GNF-GNB bacteremia, the numbers of the cases with primary bacteremia and inappropriate therapy were significantly more in EM group than those in non-EM group. Keywords: Bacteremia, Elizabethkingia meningoseptica, Glucose non-fermenting Gram-negative bacilli, Intensive care unit, Hospital mortality